VD_FINDINFO Décision / 2013 / 659 vom 10. Juni 2013 - VD Tribunal cantonal (2013)
ORDONNANCE DE CONDAMNATION, DÉFAUTCONTUMACE, OPPOSITIONPROCÉDURE | 354 CPP (CH), 356 al. 4 CPP (CH), 393 al. 1 let. b CPP (CH)